Pengaruh Teknik Relaksasi Imajinasi Terbimbing (Guided Imagery) Terhadap Pemenuhan Kebutuhan Tidur Anak Usia Sekolah di Ruang Rawat Inap Anak RSUD Prof. Dr. Ma. Hanafiah SM Batusangkar - Deswita; Asterina; Ummul Hikmah (NERS Jurnal Keperawatan, 2014)
The Influence of Guided Imagination Relaxation Techniques (Guided Imagery) toward Fulfillment of Sleeping in School-Age Children in RSUD Prof. Dr. Ma. Hanafiah SM Batusangkar Sleep disorders are often experienced by children during their hospitalization. Sleep disturbance in a long time will affect a person's physical psychological condition and can cause the length of the healing process. Guided imagery relaxation techniques is a relaxation technique that uses all the senses through audio provided. The purpose of this study was to observe the effect of guided imagery relaxation techniques to fulfill the needs of school-age children to sleep. The design of this study was a quasi-experimental design with one group pretest posttest. The sampling technique used purposive sampling the consists of 14 respondents experiencing sleep disorders. The results of this studies using Wilcoxon statistical test showed the influence of guided imagery relaxation techniques to fulfill the needs of school-age children to sleep. With an average increase in sleep duration was 8.42, p = 0.000 and 0.474 standard deviation. It should be given a guided imagery relaxation techniques, either directly or using media such as mp3 audio in a health service in improving the sleep needs of inpatient children.